Evaluation of the efficacy of 3D total-body photography with sequential digital dermoscopy in a high-risk melanoma cohort: protocol for a randomised controlled trial - Sonya Osborne; Monika Janda; Len Gray; David C Whiteman; Clare Amy Primiero; Aideen M McInerney-Leo; Brigid Betz-Stablein; Louisa Gordon; Liam Caffery; Joanne F Aitken; Elizabeth Eakin; B Mark Smithers; et al. (BMJ Open)
Introduction Melanoma is Australia’s fourth most common cancer. Early detection is fundamental in maximising health outcomes and minimising treatment costs. To date, population-based screening programmes have not been justified in health economic studies. However, a skin surveillance approach targeting high-risk individuals could improve the cost-benefit ratio.Methods and analysis This paper describes a 2-year longitudinal randomised controlled trial (RCT) to compare routine clinical care (control) with an intensive skin surveillance programme (intervention) consisting of novel three-dimensional (3D) total-body photography (TBP), sequential digital dermoscopy and melanoma-risk stratification, in a high-risk melanoma cohort. Primary outcomes will evaluate clinical, economic and consumer impact of the intervention. Clinical outcomes will evaluate differences in the rate of lesion excisions/biopsies per person, benign to malignant ratio for excisions and thickness of melanomas diagnosed. A health economic analysis using government data repositories will capture healthcare utilisation and costs relating to skin surveillance. Consumer questionnaires will examine intervention acceptability, the psychological impact, and attitudes towards melanoma risk and sun protective behaviour. Secondary outcomes include the development of a holistic risk algorithm incorporating clinical, phenotypic and genetic factors to facilitate the identification of those most likely to benefit from this surveillance approach. Furthermore, the feasibility of integrating the intervention with teledermatology to enhance specialist care in remote locations will be evaluated. This will be the first RCT to compare a targeted surveillance programme utilising new 3D TBP technology against current routine clinical care for individuals at high risk of melanoma.Ethics and dissemination This study has received Human Research Ethics Committee (HREC) approval from both Metro South Health HREC (HREC/17/QPAH/816) and The University of Queensland HREC (2018000074).Trial registration number ANZCTR12618000267257; Pre-results.